Deciphering Chemical Rules for Drug Penetration into Strongyloides - Miguel Marín; Javier Sánchez-Montejo; Sergio Ramos; Antonio Muro; Julio López-Abán; Rafael Peláez (MDPI AG, 2024)
Background: Strongyloidiasis, a parasitic infection, presents a significant public health challenge in tropical regions due to the limited repertoire of effective treatments. The screening of chemical libraries against the therapeutically relevant third-stage larvae (L3) of the model parasite Strongyloides venezuelensis yielded meager success rates. This situation is reminiscent of Gram-negative bacteria, where drug entry is a limiting factor. Methods: Here, we set out to determine whether similar barriers are in place and establish whether structural and property requirements exist for anti-strongyloides drug discovery. We focused on dyes as their uptake and effects on viability can be independently assessed in the multicellular parasite, thus providing a means to study the possibility of similar entry rules. We tested different dyes in in vitro assays on L3s. Results: We found that staining was necessary to reduce parasite viability, with some dyes achieving anti-strongyloides effects at concentrations similar to those of the reference drug, ivermectin (IV). Some dyes also showed activity against female adults at concentrations well below that of ivermectin. Unfortunately, the most potent dye, Methylene Blue, was unable to prevent the infection in a preliminary in vivo mouse model assay, presumably due to fast dye clearance. Structural analysis showed that positive charges facilitated the access of the compounds to the L3 tissue, thus providing a structural tool for the introduction of activity. For female adults, low globularity is additionally required. As a proof of concept, we added a positive charge to an inactive compound of one of our chemical libraries and re-determined the activity. Conclusions: These findings allow us to establish structural rules for parasite entry that could be of interest for future drug screening or drug development campaigns. These rules might also be applicable to other related parasites.